Effect of Frequency on Pulsed Fluidized Beds of Ultrafine Powders. (15th February 2016) - Ali, Syed Sadiq; Al-Ghurabi, Ebrahim H.; Ajbar, Abdelhamid; Mohammed, Yahya A.; Boumaza, Mourad; Asif, Mohammad
Abstract : Deagglomeration of ultrafine powders poses an important challenge towards their efficient and effective utilization. In the present study, we investigate the effect of frequency on the hydrodynamics of pulsed fluidized beds of ultrafine powders that show strong agglomeration behavior. We have carefully selected square waves of three different frequencies: 0.05 Hz, 0.10 Hz, and 0.25 Hz. The lowest frequency used here allowed the fluidized bed to settle completely before another pulse was introduced whilst the highest frequency ensured that the bed remained in a state of continuous turbulence between occurrences of consecutive pulses. On the other hand, the intermediate frequency pulse was just sufficient to complete the process of bed collapse before the start of the next pulse. Both local and global bed dynamics in all the three cases were rigorously monitored using fast response pressure transducers. The pressure transient data during the bed collapse were processed using the bed collapse model reported in the literature to compute the effective hydrodynamic diameter of agglomerates. Though there was substantial decrease in the agglomerate size, the effect of the frequency appeared to be rather insignificant as the global pressure transients remained rather insensitive to the change of the fluidization velocity.